2018
DOI: 10.1515/cclm-2017-0982
|View full text |Cite
|
Sign up to set email alerts
|

Linking type 2 diabetes and gynecological cancer: an introductory overview

Abstract: Type 2 diabetes (T2D) is a chronic disease with a growing prevalence and a leading cause of death in many countries. Several epidemiological studies observed an association between T2D and increased risk of many types of cancer, such as gynecologic neoplasms (endometrial, cervical, ovarian and vulvar cancer). Insulin resistance, chronic inflammation and high free ovarian steroid hormones are considered the possible mechanisms behind this complex relationship. A higher risk of endometrial cancer was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 146 publications
1
31
0
3
Order By: Relevance
“…The IPA core analysis of significant canonical pathways in T2DM subjects has also highlighted certain interconnected signaling pathways including P53 Signaling and Type 2 Diabetes Insulin Signaling in tandem with clear manifestations of Apoptosis Signaling , Molecular Mechanism of Cancer , Chronic Myeloid Leukemia , and Cell Cycle G1/S Checkpoint Regulation. TP53 is a central molecule that connects many of these pathways ( Figure 2 ),s consistent with previous studies [ 94 ], and has been associated with increased cancer risks among persons with T2DM [ 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Discussionsupporting
confidence: 88%
“…The IPA core analysis of significant canonical pathways in T2DM subjects has also highlighted certain interconnected signaling pathways including P53 Signaling and Type 2 Diabetes Insulin Signaling in tandem with clear manifestations of Apoptosis Signaling , Molecular Mechanism of Cancer , Chronic Myeloid Leukemia , and Cell Cycle G1/S Checkpoint Regulation. TP53 is a central molecule that connects many of these pathways ( Figure 2 ),s consistent with previous studies [ 94 ], and has been associated with increased cancer risks among persons with T2DM [ 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Discussionsupporting
confidence: 88%
“…T2DM is a known risk factor associated with pancreatic cancer 40 . A higher risk of endometrial cancer has also been observed in patients with T2DM 41 . Insulin resistance, chronic inflammation, and elevated free steroid hormones have been suggested as www.nature.com/scientificreports www.nature.com/scientificreports/ possible mechanisms involved.…”
Section: Discussionmentioning
confidence: 96%
“…Recent research shows that metformin also has an anticancer effect, functioning primarily through activation of AMP-activated protein kinase (AMPK) and regulating the activity of the AMPK/mTOR signaling pathway [17,18]. In addition, metformin can be anti-proliferative by reducing tumor vasculature through reduction in VEGF levels; increasing progesterone receptor, which increases the response to hormonal therapy; activating the AKT signaling pathway, inhibiting the IGF1R signaling pathway and reducing MRP2 expression [19][20][21].…”
Section: Discussionmentioning
confidence: 99%